Anthocyanin From Bauhinia purpurea Flower: Extraction, Color Characteristic, and Stability - Abdullah Muzi Marpaung; Darinda Pusha Djani; Della Rahmawati (Indonesian Association of Food Technologists, 2020)
The determination of the best temperature (45, 60, and 75 °C) and time (30, 75, and 120 minutes) to extract the anthocyanins from Bauhinia purpurea (BP) flower powder was studied. The anthocyanin was extracted using 40 ml of 1 N HCl/g powder with continuous shaking. Based on the total monomeric anthocyanin (TMA), the best extraction temperature and time were 45 °C and 30 minutes, respectively. The BP extract exhibited relatively high red color intensity (CI) at pH ≤ 3 and almost colorless at pH 4 – 6. Meanwhile, at pH ≥ 7, the color was unsuitable for food applications due to the high browning index. Hence, the best performance of BP extract was at pH 3. At this pH, the stability of BP extract was relatively high with the t 1/2 of CI and TMA at 30 °C was 70.30 and 72.89 days, respectively. Nevertheless, the extract was sensitive to heat as represented by the high activation energy (Ea). The Ea of CI and TMA was 64.50 kJ.mol-1 and 90.19 kJ.mol-1, respectively. The study showed the potential of BP extract as a red food colorant at pH 3 processed by relatively mild heat treatment.